PENGARUH LINGKUNGAN KERJA, PELATIHAN KERJA DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN BANYUMAS - Rafif Widianto; Suyoto Suyoto; Hermin Endratno; Totok Haryanto (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to examine the influence of the work environment, job training and workload on the performance of Banyumas District Health Service employees. This type of research is quantitative research. The research population was all employees of the Banyumas District Health Service, totaling 128 people. To determine the sample size, the Slovin formula was used, with a sample size of 97 employees. The research instrument used a questionnaire with a five-level Likert scale. The sampling technique uses Simple Random Sampling. The analysis tool uses SEM PLS. The test tool uses SmartPLS 4.0 to test validity, reliability, R-Square test, Net Fit Index (NFI) test, and hypothesis testing. The results of the analysis show that there is an influence of the work environment and workload which has a positive influence on employee performance, while job training does not have a positive influence on the performance of Banyumas District Health Service employees.